2005
DOI: 10.1254/jphs.crj04005x
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Sigma Receptors in Depression

Abstract: Abstract. Behavioral models used to test potential antidepressants have shown that ligands that bind to sigma receptors possess "antidepressant-like" properties. The focus of this review is to discuss the literature concerning sigma receptors and their ligands, with respect to their antidepressants properties. In addition to the behavioral data, we discuss electrophysiological and biochemical models demonstrating sigma receptors' ability to modulate important factors in the pathophysiology of depression and / … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
101
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(102 citation statements)
references
References 195 publications
(130 reference statements)
1
101
0
Order By: Relevance
“…A number of authors have discussed the importance of the glutamate system, e.g., [15][16][17][18] , and its regulation 19,20 . The following discussion not only addresses, glutamate, GABA, and glycine but also details how excitatory amino acids may interact with the glutamate system.…”
Section: The Glutamate Systemmentioning
confidence: 99%
“…A number of authors have discussed the importance of the glutamate system, e.g., [15][16][17][18] , and its regulation 19,20 . The following discussion not only addresses, glutamate, GABA, and glycine but also details how excitatory amino acids may interact with the glutamate system.…”
Section: The Glutamate Systemmentioning
confidence: 99%
“…Among the SSRIs, fluvoxamine was the most potent (K i ÂŒ 36 nM) for sigma-1 receptors, and paroxetine was weak (K i ÂŒ 1893 nM) for sigma-1 receptors, suggesting that these receptors may in some way play a role in the mechanisms of action of fluvoxamine (Narita et al, 1996;Hashimoto and Ishiwata, 2006). Multiple lines of evidence suggest that sigma-1 receptors play a role in the pathophysiology of neuropsychiatric diseases such as schizophrenia, anxiety disorders, and depression, as well as in the evolution of cognitive deficits associated with these conditions (Debonnel and de Montigny, 1996;Maurice et al, 2001;Su and Hayashi, 2003;Hayashi and Su, 2004;Takebayashi et al, 2004;Bermack and Debonnel, 2005;Hashimoto and Ishiwata, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Ishima and colleagues (Ishima et al 2008) showed that both sigma 1 receptors and IP 3 receptors are involved in the potentiation of NGFinduced neurite outgrowth by acetylcholinesterase inhibitor donepezil, which is known to bind to sigma 1 receptors in the brain. Accumulating evidence suggests that sigma 1 receptors are involved in both neuroplasticity and pathophysiology of neuropsychiatric diseases such as major depressive disorders, anxiety, schizophrenia and Alzheimer's disease Takebayashi et al 2004;Bermack and Debonnel 2005). Sigma 1 receptors form a trimeric complex with two other proteins on the endoplasmic reticulum: IP 3 receptor and the ankyrin isomer 220.…”
Section: Discussionmentioning
confidence: 99%